KEBIJAKAN PENEGAKAN HUKUM CYBERCRIME DAN PEMBUKTIAN YURIDIS DALAM SISTEM HUKUM PIDANA NASIONAL - Dwi Nurahman (Keadilan : Jurnal Fakultas Hukum Universitas Tulang Bawang, 2019)
This writing is oriented to find out how the legal aspects of evidence on cybercrime in the national criminal law system and law enforcement policies against cybercrime. The method uses is normatif legal research. Based on the results of the study it can be seen that the legal aspects of proving cybercrime have been strictly regulated in several laws and regulations in positive law in Indonesia. Provisions regarding Cybercrime are also regulated in international regulations without reducing the opportunity for each individual to continue to develop creativity in developing information technology. Law enforcement policies against cybercrime are carried out with a penal and non-penal approach. Seen from the point of view of criminal policy, efforts to overcome cybercrime certainly cannot be done partially with criminal law (penal), but must also be taken with an integral/systemic approach as well as a preventive approach (non-penal). Keywords : Policy; Law enforcement; Cybercrime; Proof; National Criminal Law System